The Reactualization of The Pancasila Values in The Light of Perennial Philosophy - Abdul Basir Solissa (UIN Sunan Kalijaga Yogyakarta, 2020)
The implementation of Pancasila remains a home work for all children of Indonesia. Althought has become the basis of state, Pancasila has encountered various obstacles both from the outside and the inside. This fact makes all components of the nation try to think in providing the concepts, strategies and concrete steps to place Pancasila as the living values that lead to a movement and can even bring this nation into desirable future. These efforts include the studies on the values of Pancasila from various perspectives, including that of perennial philosophy’s frame. Based on this perspective, Pancasila for the Indonesian people is actually the scientia sacra (sacred science) and kalimatun sawa (common sentences), a sacred knowledge, basic principle, and a common commitment that even existed long before the independence of Indonesia. Thus, the re-actualization of Pancasila means re-practicing its values as it has been implanted deep in the heart of this nation with a new perspective, namely that Pancasila is not merely an ideology of the state and nation, but more than that, it is actually the ontological inevitability at the heart of every human being in the Indonesian Archipelago.